The O-glycosyltransferase C1GALT1 promotes EWSR1::FLI1 expression and is a therapeutic target for Ewing sarcoma - Shahid Banday; Alok K. Mishra; Romana Rashid; Tianyi Ye; Amjad Ali; Junhui Li; Jason T. Yustein; Michelle A. Kelliher; Lihua Julie Zhu; Sara K. Deibler; Sunil K. Malonia; Michael R. Green (Nature Communications)
Abstract Ewing sarcoma (ES) is an aggressive bone cancer driven by the oncogenic fusion-protein EWSR1::FLI1, which is not present in normal cells and is therefore an attractive therapeutic target. However, as a transcription factor, EWSR1::FLI1 is considered undruggable. Factors that promote EWSR1::FLI1 expression, and thus whose inhibition would reduce EWSR1::FLI1 protein levels and function, are potential drug targets. Here, using genome-scale CRISPR/Cas9 knockout screening, we identify C1GALT1, a galactosyltransferase required for the biosynthesis of many O-glycoproteins, as a factor that promotes EWSR1::FLI1 expression. We show that C1GALT1 acts by O-glycosylating the pivotal Hedgehog (Hh) signaling component Smoothened (SMO), thereby stabilizing SMO and stimulating the Hh pathway, which we find directly activates EWSR1::FLI1 transcription. Itraconazole, an FDA-approved anti-fungal agent that is known to inhibit C1GALT1, reduces EWSR1::FLI1 levels in ES cell lines and suppresses growth of ES xenografts in mice. Our study reveals a therapeutically targetable mechanism that promotes EWSR1::FLI1 expression and ES tumor growth.